On the stabilization of the oxidized state of palladium by CuWO4 for application as catalyst in abatement of C1–C4 hydrocarbons emissions. (21st June 2019) - Gancheva, Maria; Velinova, Ralitsa; Konova, Petya; Stefanov, Plamen; Iordanova, Reni; Naydenov, Anton
Abstract: In this work for the first time we demonstrate a stabilization of Pd in its oxidation state within Pd-modified CuWO4 for application as reliable active phase in catalytic converters for abatement of exhaust gases from liquefied petroleum gas motor engines. The effect of Pd on the catalytic properties in reaction of complete oxidation of C1 –C4 hydrocarbons, the crystal structure and the chemical state have been investigated in details. The presence of supported palladium influences the system properties in respect to oxidation of organic compounds in two ways: (i) increases the reactive oxygen storage capacity of the catalyst; (ii) lowers the temperature of oxidation of the organics by enhancing the reducibility of the supporting metal oxide. The catalytic performance of Pd-modified CuWO4 is explained by partial reduction of surface Cu 2+ to Cu 1+ state, thus the copper from CuWO4 aids to avoid the reduction of PdO species during the catalytic reaction, i.e. the interaction between Pd and Cu stabilizes the oxidized Pd nanoparticles.